Experiences of Pediatric Oncology Patients and Their Parents at End of Life: A Systematic Review. (March 2016) - Montgomery, Kathleen; Sawin, Kathleen J.; Hendricks-Ferguson, Verna L.
Improvement in pediatric palliative and end-of-life care has been identified as an ongoing research priority. The child and parent experience provides valuable information to guide how health care professionals can improve the transition to end of life and the care provided to children and families during the vulnerable period. The purpose of this systematic review was to describe the experience of pediatric oncology patients and their parents during end of life, and identify gaps to be addressed with interventions. A literature search was completed using multiple databases, including CINAHL, PubMed, and PsycInfo. A total of 43 articles were included in the review. The analysis of the evidence revealed 5 themes: symptom prevalence and symptom management, parent and child perspectives of care, patterns of care, decision making, and parent and child outcomes of care. Guidelines for quality end-of-life care are needed. More research is needed to address methodological gaps that include the pediatric patient and their sibling's experience.